2012
DOI: 10.1155/2012/272694
|View full text |Cite
|
Sign up to set email alerts
|

Single-Ion Implantation for the Development of Si-Based MOSFET Devices with Quantum Functionalities

Abstract: Interest in single-ion implantation is driven in part by research into development of solid-state devices that exhibit quantum behaviour in their electronic or optical characteristics. Here, we provide an overview of international research work on single ion implantation and single ion detection for development of electronic devices for quantum computing. The scope of international research into single ion implantation is presented in the context of our own research in the Centre for Quantum Computation and Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…In other words -by means of deterministic doping, e.g. using either ion implantation (SII) [29] or so called STM-Lithography [30].…”
Section: Future Stepsmentioning
confidence: 99%
“…In other words -by means of deterministic doping, e.g. using either ion implantation (SII) [29] or so called STM-Lithography [30].…”
Section: Future Stepsmentioning
confidence: 99%
“…For ultimate doping, single ion implantation has been developed based on a FIB setup for creating custom dopant distributions with approximately 60 nm placement precision with 60 kV doubly charged Si ions, and as a result, studies of ordered dopant arrays were reported [87,88]. Single ion implantation and its applications for FETs and quantum devices were reviewed recently [89,90]. In another specialized doping scheme, FIBs are applied for the lateral patterning of two-dimensional electron gases in heterostructures [91].…”
Section: Semiconductormentioning
confidence: 99%
“…10,17,18 In earlier work, we have demonstrated single ion impact detection in micrometer scale transistors. 10,17,18 In earlier work, we have demonstrated single ion impact detection in micrometer scale transistors.…”
Section: Devices For Spin Readout and Single Ion Impact Sensingmentioning
confidence: 99%